2013
DOI: 10.1002/macp.201300552
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dual‐Thermoresponsive Phase Behavior of Zwitterionic Polysulfobetaine Copolymers Containing Poly(N,N‐dimethylaminoethyl methacrylate)‐Grafted Silica Nanoparticles in Aqueous Solution

Abstract: Novel thermoresponsive copolymers of zwitterionic sulfobetaine methacrylate (SBMA)‐ and N,N‐dimethylaminoethyl methacrylate (DMAEMA)‐grafted silica nanoparticles are prepared via surface‐initiated atom transfer radical polymerization. The phase behavior of these nanoparticles is investigated. The hybrid nanoparticles exhibit tunable phase transition temperature between the upper critical solution temperature (UCST) and the lower critical solution temperature (LCST) in aqueous solution. A high PSBMA content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
0
29
1
Order By: Relevance
“…A previous study by Yin et al demonstrated the formation of schizophrenic core−shell microgels via seeded emulsion polymerization which showed both LCST and UCST transitions . Several more studies have been carried out successfully using dual thermoresponsive systems for different biomedical applications; however, this behavior has been investigated mostly with polymeric systems such as noncrosslinked linear block copolymers. In a recent study, Yoshimitsu et al prepared a shape switching dual responsive di‐block copolymer using polymerized ionic liquid and 2‐methoxyethyl vinyl ether .…”
Section: Methodsmentioning
confidence: 99%
“…A previous study by Yin et al demonstrated the formation of schizophrenic core−shell microgels via seeded emulsion polymerization which showed both LCST and UCST transitions . Several more studies have been carried out successfully using dual thermoresponsive systems for different biomedical applications; however, this behavior has been investigated mostly with polymeric systems such as noncrosslinked linear block copolymers. In a recent study, Yoshimitsu et al prepared a shape switching dual responsive di‐block copolymer using polymerized ionic liquid and 2‐methoxyethyl vinyl ether .…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of samples is restricted by the requirement that the mobile phase must be compatible with both the analyte and the stationary phase. Common mobile phases in SEC are tetrahydrofuran (THF) [2] , [3] , [4] , [5] , [6] , dimethyl formamide (DMF) [5] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , Chloroform [4] and water [9] and common calibration standards used include polystyrene [2] , [3] , [4] , [5] , [7] , polyethylene oxide [8] or polymethyl methacrylate [5] , [6] , [10] , although many variations and alternatives have been reported [15] . However SEC measurements in eluent blends including alcohols have only been reported rarely [16] , [17] and there appears to be only one recent report on the use of methanol or ethanol as the sole component of the eluent, in an ultra high pressure SEC system [1] .…”
Section: Introductionmentioning
confidence: 99%
“…In our experience, the analysis of polyacrylamides often requires changing the eluent if pendant or chain-end functionalities are modified. Some polymers, such as poly( N -isopropyl acrylamide) (PNIPAM) are susceptible to adsorption to the stationary phase and often salts, such as tetrabutylammonium bromide (TBAB), must be added to the mobile phase to prevent interaction [12] , [23] . The use of salts requires careful control of eluent composition and in some cases salts precipitate and block components of the instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Below the critical temperature ( T C ) these polymers are soluble and they become insoluble by heating their solutions above the T C . In contrast, some polymers forming hydrogen bonds, like poly(acrylic acid) or polymers containing zwitter-ionic groups are soluble in water above a critical temperature (UCST) [67]. Only a few reports deal with polymers which have both, LCST- and UCST-behavior in water [8].…”
Section: Introductionmentioning
confidence: 99%